Measuring the macroeconomic impact of workers' remittances in a data-rich environment. - Vargas-Silva, C (Taylor and Francis, 2007)
This article uses 85 monthly time series from Mexico to study the macroeconomic impact of workers' remittances. The estimation approach is based on the two-step factor augmented vector autoregression methodology used by Bernanke et al. (2005). The results show that Mexico's inward remittances have a positive impact on prices, the stock market, interest rates and various measures of economic activity.